2021
DOI: 10.1007/s10508-021-02065-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Longitudinal Patterns of Erectile Dysfunction Drug Use Among Men Who Have Sex with Men in the U.S.

Abstract: We investigated the longitudinal relationship between erectile dysfunction (ED) drug use with behavioral factors, including substance use and sexual activities in men who have sex with men from the Multicenter AIDS Cohort Study during 1998–2016 (n = 1636). We used a bivariate random-intercept model to evaluate ED drug use along with other behavioral factors to assess relationships between the two outcomes over time on a population level and also at the individual level. Average ED drug use among men who have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This relationship is postulated to be attributed to the acute effects of drug use that can enhance sexual desire and increase intoxicating highs, thus stimulating risk-taking sexual behaviors, such as UAI, MSP [ 43 , 44 ]. In addition to illegal drugs, some popular recreational drugs that but not defined as illegal, such as rush poppers and erectile dysfunction medications, have similarly been confirmed to play a role in increasing rates of sexual risk behavior and HIV infection [ 45 , 46 , 47 , 48 ]. Furthermore, several epidemiological studies have also shown a positive dose–response relationship between frequency and number of drugs used or polydrug use and HIV risk to support our findings [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is postulated to be attributed to the acute effects of drug use that can enhance sexual desire and increase intoxicating highs, thus stimulating risk-taking sexual behaviors, such as UAI, MSP [ 43 , 44 ]. In addition to illegal drugs, some popular recreational drugs that but not defined as illegal, such as rush poppers and erectile dysfunction medications, have similarly been confirmed to play a role in increasing rates of sexual risk behavior and HIV infection [ 45 , 46 , 47 , 48 ]. Furthermore, several epidemiological studies have also shown a positive dose–response relationship between frequency and number of drugs used or polydrug use and HIV risk to support our findings [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of PDE5 inhibitors within the MSM community has been correlated with riskier sexual behavior, such as having multiple sexual partners, condomless anal intercourse, illicit drug use, and drug-enhanced sexual practices ("chemsex"). 10,17,18 Participants with more than 1 STI screening test within the study period had a markedly higher likelihood of MVAvaccination. This is reflected in other studies, where HPV vaccine uptake for MSM increased with increased health-seeking behavior, including STI screening.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in our study who obtained PDE5 inhibitor prescriptions had a higher likelihood of MVA vaccine uptake. Utilization of PDE5 inhibitors within the MSM community has been correlated with riskier sexual behavior, such as having multiple sexual partners, condomless anal intercourse, illicit drug use, and drug-enhanced sexual practices (“chemsex”) 10,17,18 …”
Section: Discussionmentioning
confidence: 99%
“…Diet and nutrition, as two of modifiable lifestyle factors, were associated with reduced total cancer-specific mortality, updated by the WCRF and the American Institute for Cancer Research (AICR) (2018) [ 38 , 39 , 40 , 41 ]. Drug use was positively correlated with sexual behaviors [ 42 ], impacting on individual HIV-infection, ultimately resulting in the increased risk of developing lung cancer for the general population [ 43 ]. Unsafe water source is present in various food products, including mutagenic and carcinogenic compounds [ 36 ].…”
Section: Discussionmentioning
confidence: 99%